Does regional ethnic diversity moderate the negative effect of school ethnic diversity on educational performance? - Sjaak Braster; Jaap Dronkers (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
This paper address the question whether ethnic diversity in school classes in the context of major cities and metropolises, where children from an early age grew up with the phenomenon of ethnic diversity, has a positive effect on the educational performance of migrant pupils. We use PISA 2006 data with 8,521 immigrant students from 35 origin countries, living in 15 destination countries, and all 72,329 native students in these countries. Native students and students with an immigrant background have been analyzed separately, using a multilevel analysis. We find that the effect of school ethnic diversity outside cities is quite negative on the educational performance of migrant and native pupils. In cities the effect of school ethnic diversity is smaller but still negative for both migrant and native pupils. But in large cities the effect of school ethnic diversity on educational performance is positive for both migrant and native pupils.
Keywords: 330